Neutrophil‐to‐lymphocyte ratio is associated with survival in patients with unresectable hepatocellular carcinoma treated with lenvatinib. (1st March 2020) - Tada, Toshifumi; Kumada, Takashi; Hiraoka, Atsushi; Michitaka, Kojiro; Atsukawa, Masanori; Hirooka, Masashi; Tsuji, Kunihiko; Ishikawa, Toru; Takaguchi, Koichi; Kariyama, Kazuya; Itobayashi, Ei; Tajiri, Kazuto; et al.
Abstract: Background and aims: Lenvatinib, a newly developed molecularly targeted agent, has become available for patients with unresectable hepatocellular carcinoma (HCC). Neutrophil‐to‐lymphocyte ratio (NLR) has been reported to be associated with poor outcomes in numerous malignancies. In this study, we investigated the impact of NLR on associating outcomes in patients with HCC treated with lenvatinib. Methods: A total of 237 patients with HCC treated with lenvatinib were included. We performed univariate and multivariate analyses in this cohort. In addition, we clarified appropriate cut‐off NLR levels for associating overall survival using hazard ratio (HR) spline curves. Results: Cumulative overall survival at 100, 200 and 300 days was 95.2%, 83.4% and 66.6% respectively. Multivariate analysis showed that NLR ≥ 4 (HR, 1.874; 95% confidence interval [CI], 1.097‐3.119), α‐foetoprotein ≥ 400 ng/mL (HR, 1.969; 95% CI, 1.188‐3.265) and modified albumin‐bilirubin grade 2b or 3 (HR, 2.123; 95% CI, 1.267‐3.555) were independently associated with overall survival. Cumulative progression‐free survival at 100, 200 and 300 days was 72.4%, 49.8% and 38.7% respectively. Multivariate analysis showed that NLR ≥ 4 (HR, 1.897; 95% CI, 1.268‐2.837) and BCLC stage ≥ C (HR, 1.516; 95% CI, 1.028‐2.236) were independently associated with progression‐free survival. Disease control rate was significantly different between the patients with low NLR (<4) (85.5%) and high NLR (≥4) (67.3%) ( P  = .007). Spline curve analysis revealed that NLR of approximately 3.0‐4.5 is an appropriate cut‐off for associating overall survival. Conclusions: NLR can be associated with outcomes in patients with HCC treated with lenvatinib.